Infrared and raman microscopy of the arsenate double salt mineral tilasite, CaMg (As04) F, from Langban, Varmland, Sweden - Kloprogge, J. Theo (2018)
This paper aims at a full description of the Raman and Infrared spectra of the arsenate mineral tilasite, CaMg(AsO4)F, from Långban, Värmland, Sweden. X-ray diffraction showed the two samples to be phase pure with a monoclinic unit cell of a = 6.683(3) Å, b = 8.950(5) Å, c = 7.572(4) Å, and β = 121.09(2)°. The infrared and Raman spectra were dominated by the arsenate modes. The two highest intensity bands were observed at 850 cm?1 and 831 cm?1 and were assigned to the Raman active ν1 symmetric stretching vibration (A1) and the Raman active triply degenerate ν3 antisymmetric stretching vibration (F2). The Raman and infrared active triply degenerate ν3 antisymmetric stretching vibration (F2) was observed in the infrared spectrum at 822 cm?1, 792 cm?1, and 761 cm?1. The intense Raman band at 465 cm?1 was assigned to the Raman active triply degenerate ν4 bending vibration (F2). The corresponding infrared bands were observed at 523 cm?1, 449 cm?1, and 414 cm?1. The intense Raman band at 329 cm?1 was attributed to the Raman active doubly degenerate ν2 symmetric bending vibration (E). Lowering of the symmetry of the tetrahedral arsenate group led to significant splitting of these modes. The low wavenumber region below 320 cm?1 was assigned to metal-oxygen stretching and lattice vibrations. In the range of 1000?1100 cm?1, four very weak bands were observed. These bands were probably due to the ν3(F2) of a very small amount of phosphate substituted for arsenate in the crystal structure of tilasite. (Author's abstract)